IMPLEMENTASI PENILAIAN AUTENTIK ASPEK SIKAP PADA PELAJARAN GEOGRAFI DI SMA NEGERI 1 SUNGAI PUAR - Nasri, Nadia; khairani, Khairani (JURNAL BUANA, 2023)
This study aims to determine the implementation of Authentic Assessment of Attitude Aspects in Geography Lessons at SMA Negeri 1 Sungai Puar. This research is motivated by the existence of an authentic assessment which is considered the right assessment to measure the extent to which students' abilities and learning outcomes are. This type of research is a quantitative descriptive research. The population in this study was SMA Negeri 1 Sungai Puar with population characteristics, namely students of class X IPS T.P 2021/2022. The sampling technique used in this study was "purposive sampling" as many as 48 students. The data analysis technique used is statistical-descriptive analysis. Statistical-descriptive analysis technique is an analytical technique by using the calculation of numbers on variables that can be measured and expressed by numbers which then the results are described in the form of sentences. The level of implementation of the authentic assessment of the attitude aspect in geography lessons at SMA Negeri 1 Sungai Puar in the implementation aspect, namely overall it is in the fairly good category with a percentage gain of 29% good, 67% quite good, and 4% not good